PENGGUNAAN MEDIA ANIMASI DALAM PEMBELAJARAN IPA PADA SISWA KELAS III.C SDN 006 TARAKAN - Diana Uno Suman; Kartini Kartini (Universitas Borneo Tarakan, 2021)
The aim of the study was to determine used of animation media as science learning in class III SDN 006 Tarakan. The type of research used Classroom Action Research (PTK). The research was carried out in 2 cycles each cycle consist of 2 meetings. The procedures for each cycle were planning, implementing, observing, and reflecting. Research subjects, 33 students consist of 18 male students and 15 female students. The data obtained in the study were student activity observation sheets and teacher activities and the data were analyzed by calculating the average. The results showed that the use of animation media as science learning in class III SDN 006 Tarakan occurred was increase where in cycle I the average value of student activity was 69 and teacher activity was 65. While in cycle II the average value of student activity was 83 and teacher activity 86. The change occurs as students can understand the material with animation media, students were motivated in learning because there was animation in learning and the teacher can provide material easily through animation media in the learning process was more effective and efficient.